2017
DOI: 10.1038/s41598-017-15250-7
|View full text |Cite
|
Sign up to set email alerts
|

RCS Diversity of Electromagnetic Wave Carrying Orbital Angular Momentum

Abstract: An electromagnetic (EM) wave with orbital angular momentum (OAM) has a helical wave front, which is different from that of the plane wave. The phase gradient can be found perpendicular to the direction of propagation and proportional to the number of OAM modes. Herein, we study the backscattering property of the EM wave with different OAM modes, i.e., the radar cross section (RCS) of the target is measured and evaluated with different OAM waves. As indicated by the experimental results, different OAM waves hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…where σ(r p , θ p , ϕ p ) is the radar cross section (RCS) of the target p(r p , θ p , ϕ p ), and it is a constant during the whole sythetic aperture, unless the OAM mode is changeable [21]. t c is the moment of the Doppler centroid; f c represents the carrier frequency; c is the speed of light; b r is the LFM ratio; w a (·) and w r (·) are the envelopes of azimuth and range; J α (·) denotes the Bessel function of the first kind, which is shown in a squared form due to the effect of both transmission and reception; k = ω/c represents the wave number; and θ(t) is the elevation angle, which is time-varying due to the relative motion between antenna and target.…”
Section: Imaging Model and Echo Signal Model Of Emv-sarmentioning
confidence: 99%
“…where σ(r p , θ p , ϕ p ) is the radar cross section (RCS) of the target p(r p , θ p , ϕ p ), and it is a constant during the whole sythetic aperture, unless the OAM mode is changeable [21]. t c is the moment of the Doppler centroid; f c represents the carrier frequency; c is the speed of light; b r is the LFM ratio; w a (·) and w r (·) are the envelopes of azimuth and range; J α (·) denotes the Bessel function of the first kind, which is shown in a squared form due to the effect of both transmission and reception; k = ω/c represents the wave number; and θ(t) is the elevation angle, which is time-varying due to the relative motion between antenna and target.…”
Section: Imaging Model and Echo Signal Model Of Emv-sarmentioning
confidence: 99%
“…It is more suitable for near-field communication, or the receiving aperture needs to be very large at long distance [21]. Other researchers have studied the scattering properties from targets by different OAM modes [22]- [25]. More researches have been done in radar imaging domain.…”
Section: Introductionmentioning
confidence: 99%
“…Although the resolution performance cannot be improved by the OAM‐based imaging radar, many simulations have demonstrated that the radar cross sections (RCSs) are different for different incident OAM waves [14, 15]. In addition, experiments were also completed to confirm that the RCSs of complex target were different for different OAM modes [16]. Compared with the plane wave, the higher signal‐to‐noise ratio (SNR) of the backscatter signal can be obtained by transmitting the appropriate OAM mode.…”
Section: Introductionmentioning
confidence: 99%